SENSITIVITY TO ANTIBIOTICS OF PLANKTON AND BIOFILM CULTURE OF STAPHYLOCOCCUS EPIDERMIDIS - О. І. Сідашенко; О. С. Воронкова; Т. М. Шевченко; О. А. Сірокваша (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2014)
The aim was to conduct the comparative analysis of the sensitivity of 20 S. epidermidis strains of plankton and biofilm to antibiotics. Methods. Identification of clinical strains of staphylococci was performed using morphological, physiological and biochemical characteristics. Sensitivity to 19 antibiotics was determined using the disc-diffusion method. The study tested the ability for film formation in 96-well plate immunoassay. Results. There were established that the sensitivity of planktonic and biofilm forms clinical isolates of S. epidermidis to antibiotics was significantly different: MIC for ofloxacin was 0.15–3.0 μg/ml (planktonic form) and 0.3–5.0 μg/ml (biofilm form); for levofloxacin respectively 0.3–1.5 μg/ml and 0.8–3.0 μg/ml; for doxycycline hydrochloride 0.5–2.0 μg/ml and 1.2–4.5 μg/ml; for ceftriaxone 8.0–15.0 μg/ml and 15.0–30.0 μg/ml; for gentamicin 4.0–15.0 μg/ml and 14.0–30.0 μg/ml. Conclusion. It is determined that MIC antibiotics that inhibit the growth of plankton cultures on average are 2–5 times less compared to MIC, inhibiting biofilm formation.